The Influence of Brand Image, Promotion and Word of Mouth on Purchasing Decisions (Case Study: Padurenan Hotmie Outlet) - Isdayanti, Rima; Yuni Astuti Tri Tartiani (Indonesian Journal of Economic & Management Sciences, 2024)
This study aims to determine the effect of brand image, promotion, and word of mouth on purchasing decisions. The research method used is descriptive quantitative. Research sampling using purposive sampling method on 100 respondents who have made purchases at Hotmie Padurenan Outlet. Data analysis with multiple linear regression calculated using SPSS 24.0. The results showed that, partially, the brand image variable had a significant effect on purchasing decisions, the promotion variable had a significant effect on purchasing decisions and the word of mouth variable had a significant effect on purchasing decisions. From the research results, the coefficient of determination (R2) value is 82%, which means that together they have an influence of 82% on purchasing decisions, while the remaining 18% is influenced by other factors outside this study